RANCANG BANGUN SISTEM KEAMANAN PINTAR PADA PINTU KAMAR MENGGUNAKAN RFID, PASSWORD DAN ANDROID BERBASIS ARDUINO UNO - Setyawan, Agus; Prabowo, Muhammad Nur; Suseno, Jatmiko Endro (BERKALA FISIKA, 2020)
The security system is very important for someone who often leaves his/her home or private room that can be used by perpetrators of crimes such as thieves. In this case, a tool is needed to anticipate this crime. Security is needed to protect ourselves and our valuable assets. In this study, a tool was used to secure a room by replacing a conventional door lock with a solenoid which can only be opened if entering passwords, cards or commands from the smartphone is correct. If entering a password or card is incorrect, then the system will lock the door automatically and sound an alarm for the specified time limit. if it is correct to enter a password or card then the system will open the solenoid and the door will open automatically without having to push the door. In addition to providing good safety, it also provides a practicality that is quite good because the door can be opened and locked automatically since we often forget ourselves to lock the door.